2020
DOI: 10.3389/fpubh.2020.579556
|View full text |Cite
|
Sign up to set email alerts
|

Learning to BREATHE “Plus”: A Multi-Modal Adaptive Supplement to an Evidence-Based Mindfulness Intervention for Adolescents

Abstract: Incorporating technological supplements into existing group mindfulness-based interventions (MBIs), particularly for use with adolescents, is an important next step in the implementation of MBIs. Yet there is little available content. Herein we present the development and content of a technological supplement for MBIs, which incorporates multiple technological elements to support (a) skill transfer from the group MBI to daily life, (b) the establishment of a formal mindfulness practice, and (c) the use of mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Mindfulness can be formal (meditation, yoga, tai chi, and other activities) or informal (walking, washing dishes, interacting with others) (Cook-Cottone, 2015). The related studies have found that mindfulness practitioners showed more stress management and coping techniques than a relaxed or self-affirming control group (Lucas-Thompson et al, 2020). Moreover, mindfulness can reduce stress by improving emotional regulation, leading to better mood and better ability to deal with stress (Wheeler et al, 2018;Li and Bressington, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness can be formal (meditation, yoga, tai chi, and other activities) or informal (walking, washing dishes, interacting with others) (Cook-Cottone, 2015). The related studies have found that mindfulness practitioners showed more stress management and coping techniques than a relaxed or self-affirming control group (Lucas-Thompson et al, 2020). Moreover, mindfulness can reduce stress by improving emotional regulation, leading to better mood and better ability to deal with stress (Wheeler et al, 2018;Li and Bressington, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological momentary interventions are another promising concept, especially in the mental health field, where cognitive and affective interventions can be delivered directly through an app [76][77][78]. Although it is possible for apps to be used for other interventions, such as driving insulin pumps in response to readings from a continuous glucose monitoring system [79] this is still unusual and very much in its infancy.…”
Section: Ecological Momentary Assessments and Interventions Are Usefu...mentioning
confidence: 99%